Zarděnkový screening testem radiální hemolýzy při aplikaci plné krve - Strauss, J; Mrázová, Marie; Švandová, Eva; Kokesová, O (Československá epidemiologie, mikrobiologie, imunologie, 1989)
The authors present the results of examination of 121 probands by the rubella test of radial haemolysis (RH), using capillary blood (direct test), as compared with the use of serum from venous blood in correlation with the rubella haemagglutination inhibition test. The diameter of the haemolytic zone, 7 mm, was as compared with the haemagglutination inhibition test in both modifications in 95% and the diameter 8 mm was seropositive in 100%. Haemolytic zones up to 6 mm must be considered seronegative even when some of the bloods or sera have bonder line haemagglutination inhibition titres. Seronegativity was expressed in the direct test of radial haemolysis by larger haemolytic zones. The specificity of the direct test of radial haemolysis, even when serum was used, was 87.5%, the sensitivity 88.2% and 88.4% resp. The reliability of positive diameters of haemolytic zones (7 mm+) is 99%, while that of negative ones (2-6 mm) only 35%. The less laborious direct test of RH proved equivalent to the radial haemolysis test using serum, as far as screening with the purpose of aimed immunization against rubella is concerned.
Keywords: Humans; Rubella virus; virus zarděnek; protilátky virové; Adolescent; mladiství; hemolytická plaková technika; Adult; Rubella; zarděnky; dospělí; Antibodies, Viral; Hemolytic Plaque Technique; lidé